Synthesis and Conformational Analysis of Some 3-Alkyl-2,6-diarylpiperidin-4-one Semicarbazones - Winfred Jebaraj, J.; Gopalakrishnan, M.; Baskar, G. (Asian Journal of Chemistry, 2010)
1H NMR and 13C NMR of several 3-alkyl-2,6-diarylpiperidin- 4-one semicarbazones 2a1, 2b1-b5, 2c1-2c3 and 2d1 have been recorded at 400 MHz. The spectral analysis data suggested that the compounds 2a1, 2b1-b5, 2c1-2c3 exist predominantly in chair conformation with the ary1 and alky1 substituents in the equatorial positions whereas 2d1 exists in boat conformation.